Opportunities and Challenges in Integrating Human Rights Education into National Curriculum in Nepal - Sahani, Indrajeet (Curriculum Development Journal, 2024)
This paper explores the integration of Human Rights Education (HRE) within Nepal’s national curriculum. The study delves into the challenges and opportunities of implementing HRE at the school level. Data was gathered through open questionnaires, discussions with school administrators and social studies teachers, and focus group discussions with students. In addition, the advice and suggestions were obtained by discussing with the headmaster of the school and the school management committee. A focus group discussion with students has been conducted on the state of human rights education in terms of activities, teaching activities, school teaching environment, and student-to-student behavior. The core theme of the study is the impact of inadequate HRE on students’ understanding and appreciation of their rights and responsibilities. This includes limitations in addressing fundamental rights, civic duties, good governance, and social issues like human trafficking and domestic violence. The analysis reveals that the current curriculum underemphasizes crucial aspects such as local history, culture, and ethical values. Furthermore, the limited teaching hours allocated to social studies compared to other subjects hinders effective HRE implementation. The study recommends increasing teaching time for social studies and incorporating a more comprehensive life skills education curriculum that prioritizes local context, harmful practices, and social values.